Meta-level control of rule execution in a parallel and distributed expert database system - Dewan, H.M.; Stolfo, S.J. (Research Issues in Data Engineering - Active Database Systems (RIDE-ADS '94), 1994)
The PARADISER system is a parallel and distributed programming environment for expert databases. It extends the memory model of expert systems to disk-resident databases, and adopts parallel and distributed processing to address expert system scaling issues. The kernel rule language, PARULEL, has parallel execution semantics and a metarule facility that allows for user-specified "programmable" conflict resolution. Under a parallel and distributed processing model of a rule language that has inherently parallel execution semantics, issues of distributed control assume paramount importance, since database consistency and synchronization must be guaranteed. We discuss various alternative strategies for implementing metarules within the PARADISER architecture.< >